A Phototheranostic Strategy to Continuously Deliver Singlet Oxygen in the Dark and Hypoxic Tumor Microenvironment. (4th February 2020) - Zou, Jianhua; Zhu, Jianwei; Yang, Zhen; Li, Ling; Fan, Wenpei; He, Liangcan; Tang, Wei; Deng, Liming; Mu, Jing; Ma, Yuanyuan; Cheng, Yaya; Huang, Wei; et al.
Abstract: Continuous irradiation during photodynamic therapy (PDT) inevitably induces tumor hypoxia, thereby weakening the PDT effect. In PDT‐induced hypoxia, providing singlet oxygen from stored chemical energy may enhance the cell‐killing effect and boost the therapeutic effect. Herein, we present a phototheranostic (DPPTPE@PEG‐Py NPs) prepared by using a 2‐pyridone‐based diblock polymer (PEG‐Py) to encapsulate a semiconducting, heavy‐atom‐free pyrrolopyrrolidone‐tetraphenylethylene (DPPTPE) with high singlet‐oxygen‐generation ability both in dichloromethane and water. The PEG‐Py can trap the 1 O2 generated from DPPTPE under laser irradiation and form a stable intermediate of endoperoxide, which can then release 1 O2 in the dark, hypoxic tumor microenvironment. Furthermore, fluorescence‐imaging‐guided phototherapy demonstrates that this phototheranostic could completely inhibit tumor growth with the help of laser irradiation. Abstract : Ein 2‐Pyridon‐basiertes Diblockpolymer (PEG‐Py) wurde zur Verkapselung des halbleitenden, schweratomfreien Photosensibilisators Pyrrolopyrrolidon‐Tetraphenylethylen (DPPTPE) verwendet. PEG‐Py kann von DPPTPE unter Laserbestrahlung generiertes 1 O2 abfangen und dieses dann in der dunklen, hypoxischen Tumormikroumgebung freisetzen. Da dieses Nanopartikel auch für die fluoreszenzgesteuerte Bildgebung nutzbar ist, könnte es auch als phototheranostisches Agens Anwendung finden.